Behavior of steel clamp confined brick aggregate concrete circular columns subjected to axial compression - Rodsin, K. (Elsevier Ltd, 2022)
Re-use of recycled aggregates in concrete has become a very sustainable solution owing to its environment-friendly and cost-effective nature. Clay bricks are most widely used in construction all over the world. Subsequently, waste generated from the demolition of clay-brick structures is most troublesome. Inherent porosity of bricks compromises the compressive strength of concrete with clay brick aggregates (C-CBA) that has rendered its use in structural concrete for quite some time. With some external clamping pressures, this deficiency can be countered. This study presents an experimental investigation into the use of steel clamps as a strengthening material for C-CBA. Steel clamps are cost-effective, readily available, and very easy to use. C-CBA were tested in two groups depending upon compressive strength: 15 & 35 MPa. Further, 3, 5, and 11 steel clamps were used in each group. Results suggested that steel clamps can effectively be used in enhancing the compressive strength of C-CBA to a level that is acceptable to be used in structural concrete. Increase in peak compressive strength of C-CBA was found to be proportional with the number of steel clamps employed. Three analytical concrete models were used to predict the compressive strength of C-CBA after strengthening. It was concluded that all three analytical models predicted well C-CBA compressive strength for 3-clamp specimens. However, their pre-diction accuracy was highly compromised as the number of steel clamps were increased. Â© 2021 The Authors